2007
DOI: 10.1128/cvi.00466-06
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibody Response to Lytic and Latent Epstein-Barr Virus Antigens in Undifferentiated Nasopharyngeal Carcinoma Patients from an Area of Nonendemicity

Abstract: Epstein-Barr virus (EBV)-associated undifferentiated carcinoma of the nasopharyngeal type (UCNT) ishighly prevalent in southeast China, where immunoglobulin A (IgA) antibodies to viral capsid antigen and early antigen (EA) represent important markers, routinely used to assist in diagnosing this malignancy. Our study aimed at determining the EBV serological profiles of 78 UCNT patients from Italy, an area of nonendemicity for this tumor, using different assays specific for both lytic and latent EBV antigens. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…One may note here that EBV is able to induce the production of IL-10 by B lymphocytes; this could suppress the antiviral immunity and enhance survival and the growth of B cells (Burdin et al, 1993). However, Tedeschi et al (2007) reported that humoral immune response decreases in very advanced stage of NPC disease. This is clearly supported by our data showing a decrease in IgG-ZEBRA titer and the persistence of a stable and very low titer of IgA-EA in adult NPC patients who died.…”
Section: Discussionmentioning
confidence: 96%
“…One may note here that EBV is able to induce the production of IL-10 by B lymphocytes; this could suppress the antiviral immunity and enhance survival and the growth of B cells (Burdin et al, 1993). However, Tedeschi et al (2007) reported that humoral immune response decreases in very advanced stage of NPC disease. This is clearly supported by our data showing a decrease in IgG-ZEBRA titer and the persistence of a stable and very low titer of IgA-EA in adult NPC patients who died.…”
Section: Discussionmentioning
confidence: 96%
“…We are aware that lack of information on EBV status in the majority of NPC cases represents a weakness of the study (32). In the subset of cases with available EBV information, all undifferentiated NPCs were EBV-positive.…”
Section: Although Cases Might Have Changed Their Dietary Habits Inmentioning
confidence: 97%
“…Several variants of Zp have been identified: Zp-P which resembles the B95-8 Zp sequence, Zp-V3, Zp-V4, and most recently Zp-PV (Gutierrez et al, 2002; Martini et al, 2007). Table 8 summarizes the distribution of Zp variants across geographic regions and health conditions (Gutierrez et al, 2002; Martini et al, 2007; Tong et al, 2003). Among controls studied, the prototype Zp-P was observed more commonly in the Americas and Europe than in China, where an almost even split was observed in the prevalence of the Zp-P and Zp-V3 variants.…”
Section: Dna Sequencingmentioning
confidence: 99%